REFORMULASI STRATEGI GUNA MENINGKATKAN TRANSAKSI DOMPET DIGITAL (STUDI KASUS PADA ACTIONPAY) - Daryanto, Daryanto; Sumardi; Andi Aswan; Kamalia; Hendra Winarta (Lembaga Intelektual Muda (LIM) Maluku, 2025)
. This study aims to reformulate an effective marketing strategy to increase the number of digital wallet transactions on the ActionPay platform. The phenomenon of declining user transaction activity is the background to the need for evaluation and reformulation of business strategies that are adaptive to the dynamics of the digital market. The location or place of the study was at the Head Office of PT. Asia Pelangi Remiten, Jakarta, the research period was two months. The population and sample were all employees of the ActionPay Digital Wallet in Indonesia, totaling 35 employees. The methodology used in this study was a qualitative approach with secondary data analysis by measuring the IFE Matrix (Internal Factor Evaluation), EFE Matrix (External Factor Evaluation), and IE Matrix. The results of the study indicate that the internal environment of the ActionPay digital wallet has a key strength in the form of a strategic partnership with Bank Syariah Indonesia which is very effective in attracting users who are sensitive to transaction costs. This partnership is a crucial asset that supports the growth and sustainability of ActionPay services in the market. However, ActionPay also faces a significant weakness, namely the lack of a deep understanding of the competitive advantages that have been established by the company among all human resources.